Foraging Behavior and Mortality of Ectatomma brunneum (Hymenoptera, Formicidae) in Simultaneous Exposure to Ant Baits and Conventional Diet in Laboratory - Tofolo, Viviane Cristina [UNESP]; Giannotti, Edilberto [UNESP]; Pizano, Marcos Aparecido [UNESP] (California State University, 2010)
The objective of this work was to identify whether the presence of leaf-cutting ant baits in the foraging arena of the ant Ectatomma brunneum (Smith) affects its foraging behavior or causes mortality in laboratory. A multiple choice test was used, composed of ant baits with three different active ingredients (sulfluramid, fipronil and chlorpyrifos) and the usual food based on proteins (Tenebrio mollitor (Linnaeus)) and carbohydrates. Using a camcorder, the observations revealed that the workers of E. brunneum stopped collecting conventional non-toxic food in order to collect toxic bait, hence causing mortality by ingestion and by contact with the active ingredients used. Although they visited the sources containing T mollitor more often, the few visits to the sources containing ant baits were enough to cause mortality of workers (14.44% with sulfluramid and 20% with chlorpyrifos and fipronil). This work showed that the brands of ant baits used, which should be selective only to leaf-cutting ants, were attractive also to this species of non-target ant.
Keywords: food choice; ants; sulfluramid; fipronil; chlorpyrifos